Peptides that inhibit the association of the surface and core antigens of hepatitis B virus - Tan, Wen Siang; Seow, Heng Fong; Yusoff, Khatijah; Ho, Kok Lian (2001)
This invention relates to isolation of high affinity binding phages carrying the fusion peptides which bind specifically to hepatitis B core antigen. A synthetic peptide derived from of the fusion peptides inhibits the association of hepatitis B surface and core antigens with an IC50 value about 10mM.